# Math virtual assistant

Calculators Topics Go Premium About Snapxam

# Step-by-step Solution

Go
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

## Answer

$x=-\frac{7}{17}$

## Step-by-step explanation

Problem to solve:

$4\left(x-1\right)\left(x+3\right)=\left(x-7\right)\left(4x+2\right)$
1

The product of two binomials of the form $(x+a)(x+b)$ is equal to the product of the first terms of the binomials, plus the algebraic sum of the second terms by the common term of the binomials, plus the product of the second terms of the binomials. In other words: $(x+a)(x+b)=x^2+(a+b)x+ab$

$4\left(x^2+2x-3\right)=\left(x-7\right)\left(4x+2\right)$
2

Solve the product $4\left(2x-3\right)$

$4x^2+8x+4\left(-3\right)=\left(x-7\right)\left(4x+2\right)$

## Answer

$x=-\frac{7}{17}$
$4\left(x-1\right)\left(x+3\right)=\left(x-7\right)\left(4x+2\right)$

Polynomials

~ 0.58 seconds